Bicoid occurrence and Bicoid-dependent hunchback regulation in lower cyclorrhaphan flies - Lemke, Steffen; Stauber, Michael; Rafiqi, Abdul Matteen; Schmidt-Ott, Urs (Evolution & development, 2008)
The homeobox gene bicoid functions as an anterior pattern organizer of the Drosophila embryo, but other than in higher flies (Cyclorrhapha), bicoid orthologues appear to be absent from insect genomes. In Drosophila, bicoid is expressed in an anterior-to-posterior protein gradient and regulates spatially restricted expression domains of segmentation genes in a concentration-dependent manner. hunchback, a direct transcriptional target of Bicoid, complements the “morphogen” activity of Bicoid. hunchback is activated by Bicoid throughout the anterior half of the blastoderm and a Bicoid-binding cis-regulatory element has been identified immediately upstream of the proximal hunchback promoter P2 of Drosophila and other higher Cyclorrhapha (Schizophora). bicoid and Bicoid-dependent hunchback regulation are thought to have originated during or before the radiation of extant Cyclorrhapha, although the precise occurrence of these traits in lower Cyclorrhapha remains unknown. Previously, we have described a bicoid orthologue in Megaselia, a species of the lower cyclorrhaphan family Phoridae. Here, we report the occurrence of bicoid in two additional lower cyclorrhaphan families, Lonchopteridae and Platypezidae. We show that Megaselia Bicoid is required for anterior expression of Megaselia hunchback, and binds upstream of its P2 promoter. Furthermore, we report the expression of lacZ reporter constructs under the control of hunchback regulatory sequences from a range of lower cyclorrhaphan and non-cyclorrhaphan flies in transgenic Drosophila embryos. Our results are consistent with a cyclorrhaphan origin of bicoid and suggest that a Bicoid-binding enhancer upstream of the hunchback P2 promoter evolved at the latest in the last common ancestor of Megaselia and Schizophora.